(untitled) (Marketing Journal, 2025)
This article examines the behavioral aspects of financial behavior among the population of Uzbekistan based on empirical research. Key factors influencing household financial decisions are identified, including financial literacy levels, trust in financial institutions, and cultural -behavioral attitudes. A comparative analysis with international data reveals both universal and Uzbekistan -specific behavioral patterns. The study offers practical recommendations for improving financial education and promoting sustainable financial behaviors.